Lithospheric flexure and gravity spreading of Olympus Mons volcano, Mars. Issue 3 (3rd March 2016) - Musiol, S.; Holohan, E. P.; Cailleau, B.; Platz, T.; Dumke, A.; Walter, T. R.; Williams, D. A.; van Gasselt, S.
Abstract: The structural architecture of large volcanoes is governed substantially by gravity‐driven deformation that is manifest as distinct processes such as basement flexure or volcanic spreading. Temporal effects and the mutual interplay of these processes have been investigated only to a limited extent, and so we present novel numerical models of the time‐dependent deformation associated with them. The models simulate the combined effects of lithospheric flexure and volcanic spreading during growth increments of an elastoplastic volcanic cone. Different spreading scenarios are considered by a variable coupling decoupling behavior at the interface between volcano and basement. We apply our models to Olympus Mons on Mars, which is characterized by upper to middle flank terraces on the shield, is encircled by a basal scarp that has an average slope of 30° and is surrounded by distant deposits that resemble large‐scale slumping features on Earth. Our results are consistent with the interpretation that terraces on Olympus Mons' flanks form by thrust faulting that results from lithospheric flexure. The presence and expression of terraces depend on the coupling of volcano and basement, on the time of volcano growth relative to mantle relaxation, and on the cohesion of the edifice. The encircling scarp may be related to a very low friction detachment at the edifice base, which leads to a normal fault regime on the lowermost flanks. With time and volcano growth, predicted stress and faulting regimes migrate only slightly, indicating that the structural architecture of volcanoes is largely set in the very early stages of formation. Key Points: Terraces on Olympus Mons volcano (Mars) are explained as thrust faults Gravity flexure in combination with spreading can account for Olympus Mons' structural arrangement A low friction at the edifice base could lead to scarp formation and collapse